THE LEISURE AS A RIGHT CROSSED FOR THE EDUCATION - Eliane Juraski Camillo (Editora da Universidade de Santa Cruz do Sul, 2011)
The present text has for intention to bring the question of the leisure and its theory, understood as a right crossed for the education, looking for to weave a reflection concerning the state of the art of the same in a society that the same lives a situation of disequilibrium in relation, where the historical pendulum seems to be hung for the work. It is paper of the education, therefore, to revert this situation not only, making possible that the man is seen as a whole, as a pair of arms for the work. Key-words: Leisure. Work. Freedom. Education. Humanization.